Rifampicin Inhibits TLR4 and IL1β Gene Expression and Enhances SH-SY5Y Cell Viability After Prolonged Ethanol Exposure in an In Vitro Experiment - Airapetov, M.I.; Eresko, S.O.; Rogova, A.S.; Bychkov, E.R.; Lebedev, A.A.; Shabanov, P.D. (Biomedical Chemistry: Research and Methods, 2024)
Prolonged alcohol exposure activates TLR4-signaling pathways in the brain, responsible for the development of neuroinflammation. There is interest in pharmacologic correction of these mechanisms. The antibiotic rifampicin (Rif) is known as a potential neuroprotectant which can correct various pathologic conditions of the nervous system associated with the development of neuroinflammatory events. We performed a study on human neuroblastoma cell culture SH-SY5Y. Prolonged incubation of SH-SY5Y cells with ethanol (24 h, 100 mM) of induced activation the innate immune system genes Tlr4 and Il1β. Pre-treatment with Rif (25-100 mM) prior to incubation of cells with ethanol inhibited Tlr4 and Il1β gene expression, whereas addition of Rif after incubation of cells with ethanol dose-dependently reduced the increased expression of Tlr4 and Il1β genes, with the most significant effect observed at a concentration of 100 mM. In addition, the use of Rif increased cell survival in culture. Thus, the results of our experiment has shown that Rif is able to eliminate the increased expression of inflammation genes caused by prolonged alcohol exposure and to increase the survival rate of long-term incubated cells in ethanol solution.